KAJIAN PENGARUH KONSENTRASI H2SO4 DAN SUHU REAKSI PADA PROSES PRODUKSI SURFAKTAN METIL ESTER SULFONAT (MES) DENGAN METODE SULFONASI - Khaswar Syamsu, Ani Suryani dan Nunung D. Putra (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTSurfactant (surface active agent) is usually used in cosmetics, laundry, and drugs industry. It's usually made from petroleum which is non renewable resources while the surfactant is non-biodegradable. The process of making surfactant from petroleum also produces high pollution. Oleochemical is one of the alternative resources for producing surfactant which be able to cover the lacks of petroleum. Methyl Ester Sulfonat (MES) is surfactant made from palm methyl ester by sulfonation reaction with sulfuric supplier agents, i.e. sulfuric acid. The aim of this research is to obtain the best condition of sulfuric acid concentration and reaction temperature of sulfonation process in methyl ester sulfonate production from palm methyl ester.The best condition for the process is performed at concentration of sulfuric acid 80% and 65 oC of reaction temperature. It produces surface tension 32,80 dyne/cm, reduction of surface tension 47,10%, interfacial tension 0,65 dyne/cm, reduction of interfacial tension 98,16%, emulsion-stability 63,32%, but has the lowest L value 57,11 in scale 0 to 100.Key words :